The impact of Human Capital and Innovation Capacity on Economic Growth in Malaysia / Nor Ezrine Yussoff, Rosnani Harun and Sa'diah Abdul Karim - Yussoff, Nor Ezrine; Harun, Rosnani; Abdul Karim, Sa'diah (2021)
Human capital, commonly understood as a set of knowledge, skills, and experience of the individuals, is known to be a catalyst of the innovation process employed in the activities that boost economic growth and development. Due to its importance, more effort to develop human capital has been emphasised by most countries. The theory of human capital has considered education as an economic production input whereas human capital development (expenditure on education or training as a proxy) refers to the acquisition and increase in the number of people who have the skills, knowledge, and experience necessary for a country's economic growth (Adelakun, 2011). Human capital development plays an important role in the Malaysian economy particularly in achieving the status of a high-income country. However, Malaysia appears to be stuck in the middle-income trap for almost 29 years. Among the reason is Malaysia has a slower rate of economic growth, higher income disparity, and a lower proportion of high-skilled employment in which the composition of the labour market is still dominated by the semi- skilled workforce (Economic Planning Unit, 2018). The availability of a skilled workforce is required to support the transition of all economic sectors to knowledge-intensive activities, the creation of new technology through innovation activities, the acceleration of labour productivity gains, and the attraction of investment into Malaysia. The government has developed strategies to achieve high skilled workforce through education such as in Malaysia Education Blueprint 2013-2025 (Preschool to Post-Secondary Education) and the Malaysia Education Blueprint 2015-2025 (Higher Education). Besides, through Eleventh Malaysia Plan (2016-2020), there is continuous agenda of producing human capital that is equipped with the right knowledge, skills, and attitudes to thrive in a globalised economy.